Effective and facile fabrication of MOFs/cellulose composite paper for air hazards removal by virtue of in situ synthesis of MOFs/chitosan hydrogel. (15th December 2020) - Nie, Jingyi; Xie, Hongbin; Zhang, Meiyun; Liang, Jiantao; Nie, Shuangxi; Han, Wenjia
Highlights: A facile strategy to fabricate MOFs/cellulose-based composite paper. The strategy coupled ZIF-8 in situ synthesis with chitosan gelation. The strategy is compatible with existing paper-making industry.More effective utilization of ZIF-8 (retention rate 75.73 %). The PM2.5 removal efficiency was 99.68 % with basis weight 60 g m −2 . The composite paper showed effective photocatalytic disinfection (inhibit zone 12 mm). Abstract: Metal-organic frameworks (MOFs) have potential in the removal of air hazards such as particulate matter. Cellulose paper is low-cost, renewable and highly industrialized matrix. A facile strategy was proposed in the present work to efficiently integrate MOFs with cellulose paper, with zeolitic imidazolate framework-8 (ZIF-8) as the model. ZIF-8 was in situ synthesis in chitosan gel and subsequently added to the cellulose pulp to fabricate composite paper. The retention rate of ZIF-8 was 75.73 %, which was significantly superior to conventional filling method (4.15 %) and in situ precipitation method (6.52 %). Moreover, ZIF-8 in the composite paper functioned well in aspects of adsorption, filtration and sterilization. The PM2.5 removal efficiency was 99.68 % with basis weight 60 g·m −2, while the removal efficiency and pressure drop can be modulated by changing the basis weight of composite paper. This strategy may offer ideas to design MOFs/cellulose-based composite materials for particulate matter removal.